2021
DOI: 10.31229/osf.io/gr2qc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Undergraduates’ Perception of Library Service Quality and Value in the 21st-Century in Southeast Nigeria: A Case Study

Abstract: The purpose of this study is to explore the undergraduates’ perception of the quality and value of library services offered to them in the 21st-century in federal universities in Southeast Nigeria. Prof. Festus Aghagbo Nwako Library (PFANL) in Nnamdi Azikiwe University Awka was used as a case study. A descriptive survey research design was adopted for the study. From a population of 14,196 registered regular undergraduates’ users of the library, a sample of 120 was selected through an accidental sampling techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…The use of ICT-based library services has been found to be on the rise, and has thereby been helpful for the respondents. This finding is supported by the studies of Udem et al (2020), Shivakumaraswamy (2019) Awotola and Adewale (2018) and Gupta and Verma (2018). When the users were asked about the level of their dependency on the library over the last three to next three years, it is noted from Table 3 that most of the users, that is, 43%, were of the view that their dependency has increased; 35% users were of the opinion that their dependency remained the same, 22% believed that their dependency on the library decreased over the last 3 years.…”
Section: Restructuring Resources In Iit Roorkeesupporting
confidence: 79%
See 1 more Smart Citation
“…The use of ICT-based library services has been found to be on the rise, and has thereby been helpful for the respondents. This finding is supported by the studies of Udem et al (2020), Shivakumaraswamy (2019) Awotola and Adewale (2018) and Gupta and Verma (2018). When the users were asked about the level of their dependency on the library over the last three to next three years, it is noted from Table 3 that most of the users, that is, 43%, were of the view that their dependency has increased; 35% users were of the opinion that their dependency remained the same, 22% believed that their dependency on the library decreased over the last 3 years.…”
Section: Restructuring Resources In Iit Roorkeesupporting
confidence: 79%
“…The use of ICT-based library services has been found to be on the rise, and has thereby been helpful for the respondents. This finding is supported by the studies of Udem et al. (2020), Shivakumaraswamy (2019) Awotola and Adewale (2018) and Gupta and Verma (2018).…”
Section: Discussionsupporting
confidence: 65%
“…and Ugwuamoke, E.C. (2020) 17 identified that the respondents perceived provision of circulation services, reference services as of good quality or effective, meritorious and encouraging. This supports the choice of our constructs in the assessment of the effectiveness of library service delivery.…”
Section: Analysis and Discussion: 91 Effectiveness Level In Service D...mentioning
confidence: 99%
“…As a result, professionalism of library staff at work should promote the image of the profession in the best possible manner on all occasions. Consequently, library staff will need to move quickly and expand their knowledge through continuing education programs, professional trainings that will enable them to fit, as they project positive image to users through their attitude and services rendered or else the library will face a continual decline in patronage particularly with the use of information communication technology (ICT) which has not only changed the role of libraries but also the users' access (Udem, Ikenwe & Ugwuamoke, 2020).…”
Section: Introductionmentioning
confidence: 99%